LANGUAGE MAINTENANCE OF BUGINESE IN BASTIONG VILLAGE, TERNATE, NORTH MOLUCCAS (A SOCIOLINGUISTIC STUDY) - Adelia Rahman; Farida Maricar; Sutisno Adam (Humano: Jurnal Penelitian, 2021)
ABSTRACT. The aim of this research is (1) to describe how the Buginese maintain their language in the society of Ternate city, especially in BastiongTalangame village and also (2) to describe the factors contributing to the maintenance of Buginese Language in BastiongTalangame village.There are two data sources that the researcher uses; they are primary data and secondary data. In analyzing the data, researcher used qualitative descriptive methods. The data was analyzed with sociolinguistic theories which intend to make the researcher easier to understand and observe how language maintenance can survive in people’s everyday lives.The findings of this study indicate that this research is spoken by the people in the house, the surrounding environment, and also in public areas such as markets that can still survive. Buginese people use Buginese language when they communicate one another. However, they use Ternate Malay when communicating with people with other tribes. It can be concluded thatn the factors contributing to the Buginese Language maintenance include social and environmental factors where they are in a region of language concentration, namely in the BastiongTalangame Village, a language attitude factor that includes language user loyalty, pride in language and also awareness of norms that are still found in maintaining language And the last factor is a migration, where the Buginese community that comes and settles in the city of Ternate.